2012
DOI: 10.2134/jeq2011.0417
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemistry and Isotopic Tracing of Nitrate Contamination of Two Aquifer Systems on Jeju Island, Korea

Abstract: The groundwater of Jeju Island (Republic of Korea) is vulnerable to contamination because its aquifers are mainly composed of highly permeable geological units and its agricultural fields are often exposed to excessive use of predominantly synthetic fertilizers. In the Gosan area of Jeju Island, we investigated nitrate contamination in both a perched aquifer above an impermeable clay bed and the regional groundwater beneath this aquitard. The δO and δD values indicate that the perched groundwater is recharged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…At the model top surface, a yearly varying recharge concentration boundary was applied. A previous study confirmed local denitrification at several perched wells (Koh et al, ). Therefore, the model included denitrification in the perched zone with a calibrated, first‐order reaction rate of 5.16E‐8 s −1 (Koh et al, ).…”
Section: Methodssupporting
confidence: 76%
See 3 more Smart Citations
“…At the model top surface, a yearly varying recharge concentration boundary was applied. A previous study confirmed local denitrification at several perched wells (Koh et al, ). Therefore, the model included denitrification in the perched zone with a calibrated, first‐order reaction rate of 5.16E‐8 s −1 (Koh et al, ).…”
Section: Methodssupporting
confidence: 76%
“…The NO 3 –N old concentration (2.2 mg/L) of the study area was taken from the measured values of the old groundwater‐dominated samples (i.e., 3 H‐free samples). The models did not consider biodegradation of nitrate because no appreciable reduction of nitrate (denitrification) was observed for the regional system (Koh et al, ). There could be some bias in the estimated nitrate loading history associated with local denitrification from the perched aquifer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In many agricultural regions, groundwater is often the major source of water both for drinking water and irrigation purposes. Groundwater contamination by nitrate derived from agricultural activities is a serious problem in many countries including Korea (Ju et al, 2006;Kaown et al, 2009;Koh et al, 2012). Understanding the sources of nitrate pollution in aquifers is a prerequisite for taking measures designed to reduce nitrate pollution of aquatic systems.…”
Section: Introductionmentioning
confidence: 99%